(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article provides a comprehensive analysis of major theories in second language acquisition (SLA), tracing their historical development, central claims, pedagogical implications, and criticisms. By examining behaviorist, innatist, cognitive, interactionist, sociocultural, and usage-based perspectives, the paper highlights how researchers have attempted to explain the internal and external factors that shape the acquisition of a second language. The article also discusses more recent approaches such as the Noticing Hypothesis, the Output Hypothesis, and Complex Dynamic Systems Theory. Through comparison of these theoretical frameworks, the discussion emphasizes that SLA is a multi-layered process encompassing linguistic, cognitive, social, and emotional dimensions. The paper concludes that no single theory fully explains SLA; instead, an integrative, interdisciplinary understanding is necessary to account for the diverse pathways through which learners develop second language competence.